Nano Enhanced Homoeopathy: Exploring the Intersection of Nanotechnologyfor Scientific Evidence in Homoeopathy A Narrative Review - Bhasin, Aditi (Indian Journal of Integrative Medicine, 2024)
Objectives: In recent years, the convergence of nanotechnology and homoeopathy has sparked intriguing discussions within the scientific and medical communities. Nanotechnology, with its ability to manipulate matter at the nanoscale, offers new avenues for enhancing the efficacy and understanding of homoeopathic remedies. This intersection has the potential to address longstanding skepticism surrounding homoeopathy by providing tangible evidence of its mechanisms of action. By exploring the applications of nanotechnology in homoeopathy, this review aims to elucidate how advancements in nanoscience are contributing to the evolution of homoeopathy as a scientifically rigorous and clinically relevant discipline. Material and Methods: Extensive research was conducted across a spectrum of articles, publications, and writings, spanning both online and offline resources, employing keywords such as nanotechnology, homoeopathy, nanoparticles, and Nanomedicine. Databases including Google Scholar, PubMed, and ScienceDirect,as well as a plethora of published books, literature, and anecdotes in homoeopathy were meticulously explored from 2010 till December 2023. This endeavour aimed at gathering comprehensive data on the utilization of nanotechnology techniques in higher dilutions to formulate scientific evidence regarding the functionality of homoeopathic medicines. Results: In the realm of homoeopathic medicine, substantial research has been conducted, particularly regarding remedies derived from metals. However, there remains a notable dearth of investigations about remedies sourced from the plant and animal kingdoms. Additionally, while considerable attention has been directed towards potencies such as 6CH, 12CH, and 30CH, recent studies have emerged focusing on the 200CH potency. Nonetheless, there exists a notable gap in research concerning higher dynamized potencies, notably 1M and 10M.Addressing this gap is crucial for advancing our understanding of homoeopathic pharmacology across a broader spectrum of potencies.